2011
DOI: 10.1002/ijc.25871
|View full text |Cite
|
Sign up to set email alerts
|

Human ZNF312b oncogene is regulated by Sp1 binding to its promoter region through DNA demethylation and histone acetylation in gastric cancer

Abstract: In a previous study, human ZNF312b was identified as a cell proliferation-associated oncogene via the K-ras/extracellular signal-regulated kinase cascade in gastric cancer. However, the mechanism concerning its transcriptional activation remains unknown. Here, we show that DNA methylation and histone acetylation of the ZNF312b promoter function as a switch for ZNF312b transcriptional activation in gastric cancer. The transcription level of ZNF312b was increased by treatment with a demethylating agent, 5-aza-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
(41 reference statements)
1
14
0
1
Order By: Relevance
“…We predicted FEZF1 as a presumed target of miR-103a-3p by miRNA target prediction software Target Scan (http://www.targetscan.org/). Studies have shown that FEZF1 played a oncogenic role through DNA demethylation [18] in gastric cancer. Nevertheless, the role of FEZF1 in GSCs remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…We predicted FEZF1 as a presumed target of miR-103a-3p by miRNA target prediction software Target Scan (http://www.targetscan.org/). Studies have shown that FEZF1 played a oncogenic role through DNA demethylation [18] in gastric cancer. Nevertheless, the role of FEZF1 in GSCs remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, expression of mitochondrial antioxidant protein Prx3 was greatly increased in CSCs isolated using CD133, CD44, and Lgr5 antibodies compared with non-CSCs (Supplementary Figure 4B). Western blot analysis confirmed that M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 11 11 confirmed elevated Prx3 expression in CD133 + cells (Supplementary Figure 4D). Furthermore, we observed increased Prx3 expression in CD133 + CSCs freshly isolated from colon cancer patients using qRT-PCR ( Figure 3A).…”
Section: Improved Mitochondrial Function Drives the Characteristics Asupporting
confidence: 76%
“…These assays were performed as described previously 11 . Detailed methods are provided in the Supplemental Information.…”
Section: Chromatin Immunoprecipitation (Chip) Assaysmentioning
confidence: 99%
“…The reduction of p21 has been validated to be caused by hypoacetylation of histone H3 [72]. By contrast, hyperacetylation in H3 of ZNF312b (FEZ family zinc finger 1) promotes the progression of gastric cancer [73]. Reduced histone H4 acetylation was found in some gastric lesions exhibiting intestinal metaplasia and has been shown to correlate with advanced tumor stage, invasion, and lymph node metastasis in gastric patients [74, 75].…”
Section: Epigenetic Biomarkers In Gastric Cancer and Their Applicamentioning
confidence: 99%